1992
DOI: 10.1111/j.1748-720x.1992.tb01215.x
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective onCruzan

Abstract: In 1990, the United States Supreme Court issued a decision in the Cruzan case, the first "right-to-die case" to reach that Court. Prior to the Court's decision, there was wide-spread speculation as to what it would decide and what the impact of the decision would be. Speculation about the impact of the decision intensified after it was announced, with many suggesting that it would prove to be a serious setback to the consensus about the legality of terminating life-sustaining medical treatment that had evolved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The Supreme Court's decision in Cruzan v. Director, Missouri Department of Health supports a patient's right to forgo PEG feeding tube insertion, through a proxy decision‐maker or advance directive, 13 but despite the consensus of the literature regarding the marginal benefits of feeding tubes in patients with advanced dementia 6,7,14 and a clear legal right to forgo a feeding tube, feeding tubes are common in patients with advanced dementia in nursing homes, whereas orders to forgo artificial hydration and nutrition are not prevalent in this population 5,15 . Furthermore, national studies have shown up to a 10‐fold difference in states in the prevalence of feeding tubes in patients with advanced dementia, suggesting that factors external to the patient's disease affect feeding tube decisions 16,17 .…”
Section: Challenges In Tube Feeding Decisionsmentioning
confidence: 99%
“…The Supreme Court's decision in Cruzan v. Director, Missouri Department of Health supports a patient's right to forgo PEG feeding tube insertion, through a proxy decision‐maker or advance directive, 13 but despite the consensus of the literature regarding the marginal benefits of feeding tubes in patients with advanced dementia 6,7,14 and a clear legal right to forgo a feeding tube, feeding tubes are common in patients with advanced dementia in nursing homes, whereas orders to forgo artificial hydration and nutrition are not prevalent in this population 5,15 . Furthermore, national studies have shown up to a 10‐fold difference in states in the prevalence of feeding tubes in patients with advanced dementia, suggesting that factors external to the patient's disease affect feeding tube decisions 16,17 .…”
Section: Challenges In Tube Feeding Decisionsmentioning
confidence: 99%